Biological and physiological role of reactive oxygen species – the good, the bad and the ugly. (29th May 2015) - Zuo, L.; Zhou, T.; Pannell, B. K.; Ziegler, A. C.; Best, T. M.
Abstract Reactive oxygen species (ROS) are chemically reactive molecules that are naturally produced within biological systems. Research has focused extensively on revealing the multi‐faceted and complex roles that ROS play in living tissues. In regard to the good side of ROS, this article explores the effects of ROS on signalling, immune response and other physiological responses. To review the potentially bad side of ROS, we explain the consequences of high concentrations of molecules that lead to the disruption of redox homeostasis, which induces oxidative stress damaging intracellular components. The ugly effects of ROS can be observed in devastating cardiac, pulmonary, neurodegenerative and other disorders. Furthermore, this article covers the regulatory enzymes that mitigate the effects of ROS. Glutathione peroxidase, superoxide dismutase and catalase are discussed in particular detail. The current understanding of ROS is incomplete, and it is imperative that future research be performed to understand the implications of ROS in various therapeutic interventions.